2018
DOI: 10.22158/jepf.v4n2p156
|View full text |Cite
|
Sign up to set email alerts
|

Government Expenditure and Poverty Reduction in Nigeria

Abstract: <p><em>This research investigates the relevance of government expenditure on poverty reduction in Nigeria. The main objective is thus to investigate whether the poverty reduction efforts through government spending has actually translated into a reduction in the poverty level. The study covered the period between 1980 and 2016. The ECM model and cointegration models of the OLS as well as the granger causality techniques were used to analyze the data. The result of the ADF unit root test indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
3
13
0
2
Order By: Relevance
“…The increase in the nation's expenditure, including the budget allocated for poverty alleviation, not only reduces the poverty gap level but also reduces the gap of the average poor person's expenditures. In general, this study is in line with Mehmood and Sadiq (2010) in Pakistan, Taruno (2019) in Indonesia, and Oriavwote and Ukawe (2018) in Nigeria.…”
Section: The Analysis Of Direct Effect Of Msmes On Poverty Reductionsupporting
confidence: 91%
“…The increase in the nation's expenditure, including the budget allocated for poverty alleviation, not only reduces the poverty gap level but also reduces the gap of the average poor person's expenditures. In general, this study is in line with Mehmood and Sadiq (2010) in Pakistan, Taruno (2019) in Indonesia, and Oriavwote and Ukawe (2018) in Nigeria.…”
Section: The Analysis Of Direct Effect Of Msmes On Poverty Reductionsupporting
confidence: 91%
“…The study found that increase in government expenditure on education stimulates growth and reduce poverty in Nigeria. Oriavwote and Ukawe (2018), examined the relationship between public spending and Poverty in Nigeria using ECM model and granger causality estimation techniques. The study revealed that public spending on education and building and construction positively impact per capita income, also, there is bi-causal relationship between public spending on education and per capita income while there is no causality relationship between public expenditure on building and construction and the per capita income.…”
mentioning
confidence: 99%
“…Under the result found by Oriavwote and Ukawe ( 2018 ), the coefficient of public expenditure has the effect of widening energy poverty. However, the coefficient of the public expenditure variable has an unexpected sign.…”
Section: Estimation Results and Discussionmentioning
confidence: 87%
“…Although income poverty, energy prices, technology, inclusive growth, and financial development are identified as the main fundamentals of energy poverty, less attention has been paid to the government policy role through public expenditure (Chien et al 2022 ; Hassan et al 2022 ; Apergis et al 2022 ). These facts make it important to study how public expenditure, more specifically, how government policies eradicate energy poverty through public expenditure (Oriavwote and Ukawe 2018 ; Nguyen and Su 2022 ).…”
Section: Introductionmentioning
confidence: 99%